Reasons why of nurses empaty with newborn families in neonatal ICU - Leandro Felipe Mufato; Maria Aparecida Munhoz Gaiva (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To understand the empathic conduct and the reasons why nurses empathize with relatives of newborns in a Neonatal Intensive Care Unit. Methods: Phenomenological research, performed in a hospital in Mato Grosso, Brazil. Data were collected between May and August 2018, through interviews with 11 nurses experienced in neonatal care, and analyzed through the lens of Alfred Schutz's Social Phenomenology. Results: Presented by two categories: nurses' empathy with family members of newborns in Neonatal ICU: empathic conduct; and, the reasons why the empathic conduct of nurses with family members in neonatal ICU. Final considerations: Empathy occurred centrally with the mother of newborns, expressed in communication, identification and construction of bonds. The reasons why the nurses' personal experiences are linked to motherhood, grief and suffering.